Alternative to what? Alternative how? A Study of Multi-Public Educational and Cultural Spaces in England since the Late Nineteenth Century - Colin, Anna (2022)
The present PhD is dedicated to the study of the foundational years of three organisations started in East London – Toynbee Hall (1884-present), Centerprise (1971 2012), and Open School East (2013-present) – which have combined the trinal functions of school, community centre, and cultural space. Multi-vision, multi-purpose, and multi public, these organisations deemed themselves alternative, whether through their pedagogical, cultural, and social engagement and practice; their governance model; and/or their conceptualisation and use of architectural space. Core to their mission were their democratic ideals of togetherness and of equality of access to education and culture, along with a preoccupation with developing participants’ agency, rebalancing power relations, and making the experience of education non-alienating and emancipatory.